STRATEGI MENINGKATKAN KEUNGGULAN BERSAING PADA PT RESTU BUMI LESTARI - Hendri Herman (JURNAL AKUNTANSI BARELANG, 2019)
This study aims to determine the strategies that can be carried out by companies in increasing competitive advantage. The object of this study is PT Restu Bumi Lestari with 45 respondents. The research data was obtained using a questionnaire. The results of this study are that prices significantly influence competitive advantage, service quality significantly influences competitive advantage, and price and service quality simultaneously have a significant effect on competitive advantage.